2020
DOI: 10.21203/rs.3.rs-36906/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A combination of herbal compound (SPTC) along with exercise or metformin more efficiently alleviated diabetic complications through down-regulation of stress oxidative pathway upon activating Nrf2-Keap1 axis in AGE rich diet-induced type 2 diabetic mice

Abstract: Background: SPTC is a mix of four herbal components (Salvia officinalis, Panax ginseng, Trigonella foenum-graeceum, and Cinnamomum zeylanicum) which might be prevented the development of AGE rich diet-induced diabetic complication and liver injury through activated the nuclear factor erythroid-2-related-factor-2 (Nrf2) pathway. Nrf2, as a master regulator of antioxidant response elements by activating cytoprotective genes expression, is decreased oxidative stress that associated with hyperglycemia and increase… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…This is because the energy required by diabetic cells is less than β-oxidation rate [ 22 ]. We speculated that most of the electron energy in ETC would be consumed for the sake of ROS production, as we observed in our previous study [ 16 ]. However, this need to be carefully elucidated in further studies.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…This is because the energy required by diabetic cells is less than β-oxidation rate [ 22 ]. We speculated that most of the electron energy in ETC would be consumed for the sake of ROS production, as we observed in our previous study [ 16 ]. However, this need to be carefully elucidated in further studies.…”
Section: Discussionmentioning
confidence: 65%
“…Some studies have shown an increase in Ucp3 expression after ingestion of Salvia and Ginseng extract (two components of SGTC) and Metformin [ 34 36 ]. Additionally, SGTC and Met antioxidant capacity might also improve the functional role of mitochondria by ROS reduction according to our previous study (Additional file 1 : Figure S2) [ 13 , 16 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The use of metformin in postmenopausal osteoporosis has not yet been investigated. Since metformin is able to improve the oxidative state in numerous diseases, including diabetes and fatty liver (11,12), the aim of the present study was to determine the role of metformin in the treatment of postmenopausal osteoporosis.…”
Section: Introductionmentioning
confidence: 99%